2019
DOI: 10.1016/j.snb.2019.04.055
|View full text |Cite
|
Sign up to set email alerts
|

Focused surface acoustic waves induced microdroplets generation and its application for microgels

Abstract: We demonstrate a novel microdroplets generation method by using focused surface acoustic waves (FSAW). The method differs from previous work in the mechanism and the geometry structure of the chip, which is depend on FSAW rather than flow shearing. The acoustic radiation force arising from FSAW acts on the oil-water interface, breaking up the water into microdroplets whose size can be controlled by tuning the driving voltage and frequency of FSAW. This approach overcomes the limitation of microchannel structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Depending on whether an external force is needed, droplet generation typically includes two types, that is, passive and active generation of microdroplets, as shown in Table 1. 58,[63][64][65][66][67][68][69][70][71][72][73][74][75][76] Passive methods require no external force, and have simple structure of the microfluidic chip. The formation of droplets is controlled mainly by modifying the microchannel structure and two-phase velocity ratio.…”
Section: Droplet Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on whether an external force is needed, droplet generation typically includes two types, that is, passive and active generation of microdroplets, as shown in Table 1. 58,[63][64][65][66][67][68][69][70][71][72][73][74][75][76] Passive methods require no external force, and have simple structure of the microfluidic chip. The formation of droplets is controlled mainly by modifying the microchannel structure and two-phase velocity ratio.…”
Section: Droplet Generationmentioning
confidence: 99%
“…3E). 69 They observed that size of the droplets was mainly determined by the frequency of the focusing surface acoustic waves, driving voltage, and velocity of the dispersed phase. Their method overcomes the limitations imposed by microchannel structure and capillary number in the general microfluidic droplet technology and has a high degree of uniformity along with a reduced system response time.…”
Section: Microfluidic Droplet Technologymentioning
confidence: 99%
“…In the prevalent oil−water systems, active control on the droplet generation has been vastly investigated. 35,36 Relevant methods include using mechanical valves, 37,38 acoustic perturbations, 39,40 and electric or magnetic actuations. 41−43 In our previous work, synchronized generation of microdroplets of largely different sizes and viscosities was achieved 44,45 using a negative resistance microfluidic oscillator.…”
Section: Introductionmentioning
confidence: 99%
“…In the prevalent oil–water systems, active control on the droplet generation has been vastly investigated. , Relevant methods include using mechanical valves, , acoustic perturbations, , and electric or magnetic actuations. In our previous work, synchronized generation of microdroplets of largely different sizes and viscosities was achieved , using a negative resistance microfluidic oscillator. In another study, we demonstrated that using a PZT actuator, the droplet size and spacing, the generation frequency, and the morphology of double emulsions can be independently controlled . However, in contrast to the oil–water system, the active generation of droplets and bubbles in a gas–liquid flow has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…SAWs have been combined into discrete microwells or microwell arrays to demonstrate the concentration of micro/nanoparticles and cells via microcentrifugation driven by the attenuation of waves in the liquid and have also been used for sensing, tissue culture, and cell culture applications. Despite growing prominence, the SAW-driven manipulation of droplets in microwells has not received much attention to date. While several SAW-induced droplet-manipulation techniques including generation, coalescence, splitting, , and steering of droplets have been demonstrated in microchannels, the manipulation of droplets in microwells using SAWs has been limited only to the ejection and coalescence of floating droplets.…”
Section: Introductionmentioning
confidence: 99%